Effects of low oxygen concentrations on aerobic methane oxidation in seasonally hypoxic coastal waters - Steinle, Lea; Maltby, Johanna; Treude, Tina; Kock, Annette; Bange, Hermann W.; Engbersen, Nadine; Zopfi, Jakob; Lehmann, Moritz F.; Niemann, Helge (Biogeosciences, 2017)
Source at https://doi.org/10.5194/bg-14-1631-2017 . Coastal seas may account for more than 75 % of global oceanic methane emissions. There, methane is mainly produced microbially in anoxic sediments from which it can escape to the overlying water column. Aerobic methane oxidation (MOx) in the water column acts as a biological filter, reducing the amount of methane that eventually evades to the atmosphere. The efficiency of the MOx filter is potentially controlled by the availability of dissolved methane and oxygen, as well as temperature, salinity, and hydrographic dynamics, and all of these factors undergo strong temporal fluctuations in coastal ecosystems. In order to elucidate the key environmental controls, specifically the effect of oxygen availability, on MOx in a seasonally stratified and hypoxic coastal marine setting, we conducted a 2-year time-series study with measurements of MOx and physicochemical water column parameters in a coastal inlet in the south-western Baltic Sea (Eckernförde Bay). We found that MOx rates generally increased toward the seafloor, but were not directly linked to methane concentrations. MOx exhibited a strong seasonal variability, with maximum rates (up to 11.6 nmol L−1 d −1 ) during summer stratification when oxygen concentrations were lowest and bottom-water temperatures were highest. Under these conditions, 2.4–19.0 times more methane was oxidized than emitted to the atmosphere, whereas about the same amount was consumed and emitted during the mixed and oxygenated periods. Laboratory experiments with manipulated oxygen concentrations in the range of 0.2–220 µmol L−1 revealed a submicromolar oxygen optimum for MOx at the study site. In contrast, the fraction of methane–carbon incorporation into the bacterial biomass (compared to the total amount of oxidized methane) was up to 38-fold higher at saturated oxygen concentrations, suggesting a different partitioning of catabolic and anabolic processes under oxygen-replete and oxygen-starved conditions, respectively. Our results ...